Comparison of the Demographics and Ratio of Rotavirus-Associated Benign Convulsions with Mild Gastroenteritis to Rotavirus Gastroenteritis before and after Rotavirus Vaccination over a Period of 20 Years - Yeong Seok Lee; Dong Hyun Kim; Dong Jun Ha; Young Se Kwon (Korean Child Neurology Society, 2021)
Purpose Through a study of rotavirus gastroenteritis (RVGE) cases experienced over 20 years at our center, we aimed to investigate changes in the ratio of rotavirus-associated benign convulsions with mild gastroenteritis (RaCwG) to RVGE and in patients' demographics after rotavirus vaccination. Methods We analyzed the data of patients aged ≤6 years who visited Inha University Hospital between January 1999 and December 2019 and were confirmed to have RVGE. Patients were divided according to whether they had convulsions with mild gastroenteritis, and their demographics were compared. The yearly and monthly ratios of RaCwG to RVGE were evaluated. To investigate the effects of rotavirus vaccination, data regarding demographics and prevalence were divided into periods I (pre-vaccination, 1999-2009) and II (post-vaccination, 2010-2019) and compared. Results Altogether, 2,100 children had RVGE, and 50 (2.4%) had RaCwG. RaCwG occurred frequently every 4 to 6 years. Although the total number of RVGE and RaCwG cases significantly decreased in period II versus period I, the ratio of RaCwG to RVGE did not differ between the two groups (P=0.921). The age distribution shifted upwards in period II versus period I (P=0.001), but the sex ratio and seasonal distribution showed no significant difference. Conclusion Considering that the ratio of RaCwG to RVGE is dynamic, an increase in the ratio of RaCwG may be possible in the future. Although there was no change in the ratio of RaCwG to RVGE, the number of RVGE and RaCwG patients decreased simultaneously, suggesting that rotavirus vaccination was effective in preventing RaCwG.